Career Preferences of Graduating Medical Students in Universiti Malaysia Sabah - Ng Chiak Yot; Khor Foo Kiang; Constance Liew Sat Lin; Symeon Mandrinos; Fairrul Kadir; Malehah Mohd Noh; Nagesh Chodankar; Chandrika Murugaiah; Mohd Nazri Mohd Daud; Nelbon Giloi; May Zaw Soe; Ehab Helmy Abdel Malek Fahmy; et al. (Malaysian Journal of Medicine and Health Sciences, 2020)
Health workforce education and training is a complex investment, which align education, finance, labour market and policies. Most medical universities have limited residency programs to satisfy the postgraduate career preference and lack of supervision career and social orientations to medical students which lead to misunder¬standings of personal learning plans and preferences in medical profession. Therefore, this study aimed to examine medical students’ career choices and altitudes towards medical instruction in preparing the medical students to work in rural and remote areas of Sabah. Methods: 98 First and 95 fifth year medical students were obtained consent to answer UMS Career Study Questionnaire consisting 29 questions on (1) medical schools - school career orientation; (2) students- study year; (3) student values- academic performance, and attitudes; (4) satisfaction- salary, secure, workload. (5) Perception on specialty (6) perception of potential benefits. Results: The first three selected specialties of choices for postgraduate training. Obstetrics and Gynaecology 26 (15.2%), surgery 23 (13.5%), paediatrics and child health 18 (10.5%) of the medical students, respectively. The main reasons for specialty preferences were oppor¬tunity to learn community health problems (35%), adequate time to study in rural health facilities (28%) and privilege for specialty training (24%), family live in rural area (20%). Conclusions: Medical students’ inclination towards few clinical specialties might raise a concern in shortage in various clinical speciality areas.